2014
DOI: 10.1177/0193945914522862
|View full text |Cite
|
Sign up to set email alerts
|

Medical Assistant Coaching to Support Diabetes Self-Care Among Low-Income Racial/Ethnic Minority Populations

Abstract: Innovative, culturally tailored strategies are needed to extend diabetes education and support efforts in low-resourced primary care practices serving racial/ethnic minority groups. A randomized controlled trial examined the effect of a diabetes self-care coaching intervention delivered by medical assistants and the joint effect of intervention and ethnicity over time. The randomized repeated-measures design included 270 low-income African American and Hispanic/Latino patients with type 2 diabetes. The one-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 35 publications
1
67
0
Order By: Relevance
“…A positive change in the self-care activities as indicated by increased self-care scale scores after education and telephone follow-up demonstrates that regular monitoring of patients is beneficial. In previous studies on diabetic patients, education 3,18,19 and telephone-delivered follow-up 11,12,20,21 have been found to have a positive influence on self-care behaviors of patients. The telemedicine intervention was shown to be related to improved self-efficacy, which was directly and indirectly associated with improved glycemic control.…”
Section: Discussionmentioning
confidence: 94%
“…A positive change in the self-care activities as indicated by increased self-care scale scores after education and telephone follow-up demonstrates that regular monitoring of patients is beneficial. In previous studies on diabetic patients, education 3,18,19 and telephone-delivered follow-up 11,12,20,21 have been found to have a positive influence on self-care behaviors of patients. The telemedicine intervention was shown to be related to improved self-efficacy, which was directly and indirectly associated with improved glycemic control.…”
Section: Discussionmentioning
confidence: 94%
“…5 They also serve as health coaches to improve lifestyle behaviors 9 , chronic disease care processes 3,10 -18 , and medication adherence. 19 These innovative MA roles have been reported across diverse settings, including private practices 2,3,5,20 , community health centers 5,10,13,15,16,19 , academic primary-care practices 8,9,12,14 , rural practices 17 , and large health care systems. 4,5,7 Outcomes in studies that have focused on or included MA role expansion or innovation have varied.…”
mentioning
confidence: 99%
“…9 However, Ferrer and colleagues 2 found that there was poor adoption of MA health coaching, and several randomized trials testing the effects of MA diabetes health coaches found no significant differences in hemoglobin A1C levels or hospitalizations between control and intervention group patients. 10,13,15,18 There is currently a limited understanding as to why there was success in some studies and not others.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of diabetes care, which addresses prescribed self-care goals, evidence exists of improvement in self-care using health coaching with a MA. 20 Among people with uncontrolled diabetes, hypertension, or hyperlipidemia, in-clinic health coaching by MAs over one year improved biomarkers of health risks. 9 We explored the feasibility of training MAs to address health coaching for improved nutrition, physical activity, and sleep among the general clinic population.…”
mentioning
confidence: 99%